Preparation method of fabricated ancient building wall body with phase change heat preservation function
By using modified expanded perlite slabs as the insulation material for ancient building walls, the problems of flammability and insufficient adhesion of organic materials such as polystyrene boards are solved, and good flame retardancy and temperature adjustment effects are achieved.
Patent Information
- Application Number
- CN202510046643.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-04
AI Technical Summary
The organic insulation materials such as polystyrene boards used in existing ancient building walls have problems such as flammability, poor strength, poor load-bearing capacity and poor adhesion, resulting in poor fire resistance and easy separation of water leakage between layers.
Expanded perlite slabs with phase change insulation are used to prepare expanded perlite slabs with phase change insulation by combining modified expanded perlite and water glass adhesives.
It improves the insulation performance of the insulation material, has good flame retardancy and temperature adaptive adjustment functions, and can keep the indoor temperature between 18-30℃ in an outdoor environment of 12-38℃, solving the problems of fire resistance and insulation performance of ancient building walls.
Smart Images

Figure CN119748606A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing an assembled ancient building wall, and in particular to a method for preparing an assembled ancient building wall with a phase-change thermal insulation function. Background Art
[0002] Traditional wall construction in ancient buildings is often plagued by complex processes, high pollution levels, significant material consumption, and uncontrollable energy-saving coefficients. To develop a greener, more energy-efficient, and efficient ancient building construction system, we are specifically researching and applying prefabricated construction methods specifically for walls in these buildings. Prefabricated buildings are structures assembled on-site using prefabricated components. For example, building walls are prefabricated in a factory. On-site construction requires only the prefabricated walls to be installed in designated locations and then cast into shape. Prefabricated buildings offer ease of installation, a short construction cycle, and consistent structural quality, enabling the formation of an industrialized production and processing system.
[0003] In addition to the concrete and decorative finishes, the walls of historic buildings also contain an insulation layer. Currently, the most common prefabricated sandwich insulation system consists of two layers of reinforced concrete wall panels, with insulation material sandwiched between them, connected by specialized connectors. The exterior wall panels, with specific insulation performance requirements, effectively protect the interior wall panels and insulation material. Currently, polystyrene insulation is a popular choice for this insulation layer. With its low density and unique honeycomb structure, polystyrene effectively blocks heat conduction and has a low thermal conductivity. It also offers lightweight, high compressive strength, superior water and moisture resistance, corrosion resistance, durability, a long service life of 30-40 years, and ease of construction. The inventor's previously proposed invention patent CN118181503 discloses a method for preparing an assembled ancient building wall. The assembled ancient building wall has a thickness of 210-330 mm and includes, from the exterior wall to the interior wall, a 30-50 mm thick facing brick layer, a 40-60 mm thick outer concrete layer, a 60-100 mm thick insulation layer, and an 80-120 mm thick inner concrete structural wall layer. The insulation material of the insulation layer is molded polystyrene board, extruded polystyrene board, or foamed polystyrene board. Utility model patent CN207211470U also discloses an energy-saving antique building roof, including a vertical roof panel vertically arranged within the wall and an inclined roof panel inclined relative to the vertical roof panel. A storage space is formed between the inclined roof panel and the vertical roof panel. The storage space is sequentially laid from bottom to top with a first waterproof membrane layer, an insulation layer, and a fine stone concrete layer. Wooden rafters are erected above the fine stone concrete layer, and a small green tile roof is laid above the wooden rafters. The beneficial effects of the present invention are as follows: the first waterproof membrane layer, the thermal insulation layer, and the fine stone concrete layer are arranged in the accommodation space and wrapped with wooden rafters, thereby reducing the thickness of the roof and making it more beautiful in appearance; laying SBS waterproof membrane has a good waterproof effect; laying extruded polystyrene boards has a good thermal insulation effect and is more energy-efficient. It can be seen that in building structures, especially in the walls of ancient buildings, the use of organic thermal insulation materials such as polystyrene boards is the current mainstream technology. However, it is undeniable that thermal insulation materials such as polystyrene boards also have the problems of being flammable, having poor strength, poor load-bearing capacity, and poor adhesion between organic materials and concrete inorganic materials. This leads to the problems of poor fire resistance, weak adhesion, and easy separation and leakage between layers in the walls of ancient buildings using organic thermal insulation materials such as polystyrene boards.
[0004] Because the combustion performance of the insulation materials in the wall external insulation system does not meet the national standard requirements, fire accidents in construction projects have occurred frequently, causing serious casualties and property losses. In order to deeply learn the lessons of fire accidents and curb the current high incidence of fires caused by external insulation materials, the Ministry of Public Security issued the "Notice on Further Clarifying the Relevant Requirements for Fire Supervision and Management of External Insulation Materials for Civil Buildings", requiring that the external insulation materials of civil buildings use materials with combustion performance of Class A.
[0005] Inorganic insulation boards, such as rock wool, foam glass mud, foam ceramic, and expanded perlite, often used in insulation boards, have advantages over polystyrene boards, such as superior adhesion, fire resistance, and high strength. For example, CN 105439529A discloses an alkali-reversion-inhibiting perlite insulation board and its production method. The alkali-reversion-inhibiting perlite insulation board is made from expanded perlite, water glass, a hydrophobic agent, an inhibitor, water, and an adhesive. The water glass, hydrophobic agent, and water are weighed and mixed uniformly, then added to the expanded perlite. After stirring, the mixture is poured into a mold and pressed into shape to produce a wet base plate. The base plate is then microwave-dried to a constant weight. The inhibitor and adhesive are pre-mixed to obtain a mixture, the surface of the base plate is then sprayed with water, and the mixture is evenly applied to the pretreated base plate. The alkali-reversion-inhibiting perlite insulation board produced by this method can solve the problem of alkali reversion on the surface of perlite insulation boards with water glass as adhesive without basically increasing the cost, improve the weather resistance of the perlite insulation board, improve the appearance of urban buildings, and avoid accidents caused by peeling of the external insulation layer of the exterior wall.
[0006] Fire resistance is a particular concern for ancient architecture. Therefore, ancient building complexes using ancient architectural walls typically have a significant amount of wood, compared to modern structures. Consequently, fire resistance requirements are higher than those for conventional buildings. Furthermore, antique-style architecture also places extremely high demands on the thermal insulation performance of its walls. The use of modern electrical appliances like air conditioners not only detracts from the overall style of the ancient complex, but excessive electrical equipment also poses a fire hazard. Consequently, the ancient building materials industry is in great demand for building materials that combine thermal insulation and flame retardancy, a requirement currently unavailable in the materials used in ancient architecture. Summary of the Invention
[0007] In order to solve the above technical problems, the present invention provides a method for preparing an assembled ancient building wall with phase change thermal insulation function, which uses expanded perlite board, an inorganic thermal insulation material, to improve the thermal insulation performance of the thermal insulation material and has phase change thermal insulation performance, so that the prepared ancient building wall and the manufactured building have temperature adaptive regulation.
[0008] In order to achieve the above-mentioned object, the present invention discloses a method for preparing an assembled ancient building wall, wherein the assembled ancient building wall has a thickness of 210-330 mm, preferably 250-300 mm, and comprises, from the outer wall to the inner wall, a 30-50 mm face brick layer, a 40-60 mm concrete outer page layer, a 60-100 mm insulation layer, and an 80-120 mm concrete structure wall inner page layer. The preparation method comprises the following steps: 1) cleaning the mold; 2) arranging the bricks, using a sponge 1) Fill the gaps with strips to form the facing brick layer, and groove the side of the facing brick layer closest to the concrete outer layer; 2) Fill the gaps with cement mortar; 3) Apply an interface agent; 4) Lay the first layer of rebar and install embedded tie bars for the upper and lower layers; 5) Pour concrete to form the concrete outer layer; 6) Lay the insulation layer; 7) Lay the second layer of rebar, connect the first and second layers, and pre-embed water and electricity pipelines, lifting parts, and connectors; 8) Pour the inner layer of the concrete structure wall; 9) De-mold, maintain, and inspect the wall. The wall is a sill wall, gable wall, or rear eaves wall. The concrete in the inner layer of the concrete structure wall is preferably lightweight aggregate concrete.
[0009] The facing brick layer is made of small-sized mud bricks. The sill wall is produced using a dry-laying process, using Haitangchizi hard-core square bricks as the core. Dry-laying wall bricks should be tested face-on beforehand. After the face-on testing confirms the correctness of each brick joint, they are reversed and placed in a mold. The gable wall is produced using a moon-white ash soft-core wall process, with a reserved plaster thickness for the soft-core wall. The rear eaves wall is produced using a small-sized mud-whitening process.
[0010] The thermal insulation material of the thermal insulation layer is expanded perlite board with phase change thermal insulation function.
[0011] The raw materials for preparing the expanded perlite board include 100 parts by weight of modified expanded perlite with phase change thermal insulation function, 50-70 parts by weight of water glass type adhesive, 3-8 parts by weight of water repellent, 10-20 parts by weight of fiber, and 10-30 parts by weight of water.
[0012] The water glass type adhesive is composed of 40%-60% of sodium water glass, 20%-40% of potassium water glass, and 20%-30% of silica sol in terms of weight percentage;
[0013] The water repellent is a silicone water repellent;
[0014] The fibers are polypropylene chopped fibers;
[0015] Its preparation method consists of the following steps:
[0016] Step A: Premixing: uniformly mixing the water glass adhesive, water repellent, fiber, and water according to the raw material measurement to obtain a premix A;
[0017] Step B: Mixing: mixing the premix A with the modified expanded perlite;
[0018] Step C: pressing and molding the slurry prepared in step B using a mold to obtain a slab;
[0019] Step D: Drying and shaping, after demoulding, drying is carried out at a drying temperature of 70-120°C and a drying time of 7-12 hours to obtain an expanded perlite board with phase change thermal insulation function, and the product is inspected and released.
[0020] The addition of silica sol can improve the bonding strength of the adhesive; potassium water glass and sodium water glass are mixed because potassium water glass has better disintegration and better water resistance.
[0021] The modified expanded perlite with phase change and heat preservation function is prepared as follows:
[0022] (1) Infiltrating organic phase change material into expanded perlite;
[0023] Add expanded perlite to a vacuum reactor at 40-60° C., then evacuate the reactor to a negative pressure of 0.06-0.08 MPa, close the exhaust valve, and add the liquid organic phase change material while stirring for 10-20 minutes; then open the exhaust valve, adjust the negative pressure of the vacuum reactor to 0.085-0.095 MPa, and continue stirring for 40-120 minutes so that the organic phase change material is fully absorbed by the expanded perlite; stop stirring, and adjust the pressure to normal pressure to obtain an organic phase change material composite expanded perlite A;
[0024] Wherein, by weight, the ratio of expanded perlite to organic phase change material is 10:(6-9);
[0025] Wherein, in the organic phase change material, the ratio of n-tetradecane:n-hexadecane:n-octadecane is 1:(0.5-1.5):(1-3), preferably 1:1:2;
[0026] (2) at room temperature, uniformly mixing acrylic acid, sodium hydroxide, acrylamide, an initiator, and water to obtain a solution 1 to be reacted;
[0027] The organic phase change material composite expanded perlite A prepared in step (1) is added to a reactor with a vacuum degree of 0.08-0.095 MPa, and the reaction solution 1 is added while stirring for 0.5-6 hours, and then the stirring is stopped to obtain the modified expanded perlite. The obtained modified expanded perlite is then placed in a reactor and heated at a temperature of 70-90°C for 0.5-1 hour under normal pressure to obtain the modified expanded perlite B;
[0028] The mass ratio of acrylic acid, sodium hydroxide, acrylamide and organic phase change material composite expanded perlite A is (10-20): (4-8): (2-3): 100;
[0029] Wherein, the initiator is potassium persulfate or sodium persulfate;
[0030] (3) At room temperature, acrylate, silane, photoinitiator, and thermal initiator are added to a reactor and stirred to obtain a solution 2 to be reacted; the modified expanded perlite B prepared in step (2) is immersed in the above-mentioned solution 2 to be reacted, while stirring, and the immersion time is 30 minutes to 6 hours, and the stirring is stopped and filtered to obtain the modified expanded perlite, and the above-mentioned filtrate can be reused; the obtained modified expanded perlite is then subjected to UV radiation curing for 0.5-1 hour; the modified expanded perlite is then placed in an oven and heated for 20-40 minutes at a heating temperature of 70-90°C to obtain a modified expanded perlite finished product with phase change and heat preservation function;
[0031] Wherein, the acrylate is methyl (meth)acrylate, ethyl (meth)acrylate, β-hydroxyethyl (meth)acrylate, preferably ethyl (meth)acrylate;
[0032] Wherein, the silane is γ-methacryloxypropyltrimethoxysilane (KH570);
[0033] Wherein, the photoinitiator is benzoin ethyl ether, α,α-dimethoxy-α-phenylacetophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxy-cyclohexyl phenyl ketone, benzophenone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide or diarylphosphine oxide;
[0034] Wherein, the thermal initiator is potassium persulfate or sodium persulfate;
[0035] The mass ratio of acrylate, silane, photoinitiator, thermal initiator and expanded perlite B is (100-150):(40-50):(2-3):(2-3):10.
[0036] The present invention has the following beneficial effects:
[0037] (1) Compared with the inventor's previous technology, the present invention adopts the inorganic thermal insulation material expanded perlite board. While having the flame retardancy commonly possessed by inorganic materials, the thermal insulation performance of the thermal insulation material is improved by modifying the perlite, and the thermal insulation performance of the thermal insulation material is improved, and the thermal insulation performance is also possessed by phase change thermal insulation performance, so that the prepared ancient building walls and manufactured buildings have temperature adaptive regulation, which is not only warm in winter and cool in summer, but also most of the indoor temperatures can be stabilized between 18-30 °C.
[0038] (2) The present invention uses organic phase change materials with different phase change temperatures, such as n-tetradecane, n-hexadecane, and n-octadecane, to compound. n-octadecane with a phase change temperature of 28°C is used as the main phase change material, and n-tetradecane and n-hexadecane with slightly lower phase change temperatures are used to coordinate. Through appropriate formulation, a phase change material system that can adapt to outdoor temperatures in different seasons in a step-by-step manner is obtained. Under outdoor environmental conditions of 12-38°C, the indoor temperature can be stabilized between 18-30°C.
[0039] (3) In order to overcome the problem of leakage of organic phase change materials in porous inorganic materials in the prior art, the inventors tried to prepare polyacrylic acid water-absorbing resin in perlite by in-situ preparation after filling the organic phase change material. By utilizing the water absorption and expansion properties of the resin, not only was the inner layer of organic phase change material sealed in the perlite, but the resin itself also contained a large amount of water and was also a good thermal insulation phase change material, which could further improve the thermal insulation performance.
[0040] (4) To avoid the adverse effects of perlite moisture on the water glass adhesive in the perlite board, the present invention further utilizes a highly waterproof acrylic ester to copolymerize with a silane monomer, and utilizes UV radiation curing followed by thermal initiation curing to achieve secondary sealing and complete coating of the perlite, while also improving the uniformity of the perlite surface coating. The introduction of the silane copolymer monomer also enhances the hydrophobicity of the perlite, enabling it to encapsulate the organic phase change material, water-absorbing resin, and water. Furthermore, the hydrophobicity of the silane improves the compatibility of the perlite with water glass, thereby increasing the bonding strength and overall strength while also avoiding and reducing the alkali backflow phenomenon of the inorganic thermal insulation layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 A schematic structural diagram of the present invention
[0042] In the accompanying drawings: 1, facing brick layer, 2, outer page layer, 3, insulation layer, 4, inner page layer. DETAILED DESCRIPTION
[0043] The technical solution of the invention is described in detail below with reference to specific embodiments.
[0044] Example 1 Preparation of modified expanded perlite with phase change and thermal insulation function
[0045] (1) Infiltrating organic phase change material into expanded perlite
[0046] The expanded perlite was added to a vacuum reactor at 50° C., and then the vacuum reactor was evacuated to a negative pressure of 0.07 MPa. The exhaust valve was closed, and the liquid organic phase change material was added while stirring for 15 minutes. The exhaust valve was then opened, and the negative pressure of the vacuum reactor was adjusted to 0.09 MPa. The stirring was continued for 60 minutes so that the organic phase change material was fully adsorbed by the expanded perlite. The stirring was stopped, and the pressure was adjusted to normal pressure to obtain an organic phase change material composite expanded perlite A. The ratio of the expanded perlite to the organic phase change material was 10:8 by weight, and the ratio of the n-tetradecane to the n-hexadecane to the n-octadecane in the organic phase change material was 1:1:2 by weight.
[0047] (2) At room temperature, acrylic acid, sodium hydroxide, acrylamide, an initiator, and water are uniformly mixed to obtain a solution 1 to be reacted; the organic phase change material composite expanded perlite A prepared in step (1) is added to a reactor with a vacuum degree of 0.09 MPa, and the solution 1 to be reacted is added while stirring for 1 hour, and then stirring is stopped to obtain a modified expanded perlite. The obtained modified expanded perlite is then placed in a reactor under normal pressure and heated at 80° C. for 0.5 hour to obtain a modified expanded perlite B.
[0048] The mass ratio of acrylic acid, sodium hydroxide, acrylamide and organic phase change material composite expanded perlite A is 12:4:2:100; and the initiator is potassium persulfate or sodium persulfate.
[0049] (3) At room temperature, acrylate, silane, photoinitiator and thermal initiator are added to a reactor and stirred evenly to obtain a solution 2 to be reacted; the modified expanded perlite B prepared in step (2) is immersed in the above-mentioned solution 2 to be reacted, and stirred at the same time. The soaking time is 1 hour, and the stirring is stopped and filtered to obtain the modified expanded perlite, and the above-mentioned filtrate can be reused; the obtained modified expanded perlite is then UV-cured for 0.5 hours; the modified expanded perlite is then placed in an oven and heated for 30 minutes at a heating temperature of 80°C to obtain a modified expanded perlite finished product with phase change and thermal insulation function; wherein the acrylate is methyl (meth)acrylate, the silane is γ-methacryloyloxypropyltrimethoxysilane (KH570), the photoinitiator is α,α-dimethoxy-α-phenylacetophenone, the thermal initiator is sodium persulfate, and the mass ratio of acrylate, silane, photoinitiator, thermal initiator and modified expanded perlite B is 120:40:2.5:2.5:10.
[0050] Example 2 Preparation of expanded pearlite board with phase change thermal insulation function
[0051] The raw materials for preparing the expanded perlite board include 100 parts by weight of the modified expanded perlite with phase change thermal insulation function prepared in Example 1, 60 parts of a water glass type adhesive, 5 parts of a water repellent, 15 parts of fiber, and 20 parts of water; the water repellent is an organic silicone water repellent; the fiber is polypropylene chopped fiber; the water glass type adhesive is composed, by weight, of 50% sodium water glass, 30% potassium water glass, and 20% silica sol; and the preparation method comprises the following steps:
[0052] Step A: Premixing: uniformly mixing the water glass adhesive, water repellent, fiber, and water according to the raw material measurement to obtain a premix A;
[0053] Step B: Mixing: mixing the premix A with the modified expanded perlite;
[0054] Step C: pressing and molding the slurry prepared in step B using a mold to obtain a slab;
[0055] Step D: Drying and shaping, after demoulding, drying is carried out at a drying temperature of 110°C and a drying time of 8 hours to obtain an expanded perlite board with phase change thermal insulation function, and the product is inspected and released.
[0056] Example 3 Preparation of Prefabricated Ancient Building Threshold Wall A
[0057] The thickness of the assembled ancient building threshold wall is 270mm thick, specifically including a 40mm thick face brick layer 1, a 50mm thick outer page layer 2, an 80mm thick insulation layer 3 and a 100mm thick inner page layer 4. The face brick layer 1 is a small stop mud face brick layer, the outer page layer 2 is a concrete outer page layer, the insulation layer 3 can be a thermal insulation layer obtained by cutting the expanded perlite board with phase change insulation function prepared in Example 2, and the inner page layer 4 is a lightweight aggregate concrete structure wall inner page layer, comprising the following steps: 1) cleaning the mold; 2) arranging the bricks and plugging the seams with sponge strips to obtain The following steps are performed: 1) grooving the facing brick layer, wherein the cross-sectional shape of the groove is a trapezoidal structure, which is wide at the bottom and narrow at the top; 2) grouting with cement mortar; 3) applying the epoxy interface agent prepared in Example 1; 4) laying the first layer of steel bars, and setting the upper and lower layers of steel bar tie embedded parts; 5) pouring the outer concrete page to obtain the outer page layer; 6) laying the insulation layer; 7) laying the second layer of steel bars, connecting the first and second layers of steel bars, and pre-buried the water and electricity pipelines, hoisting parts, and connecting parts; 8) pouring the inner page layer of the lightweight aggregate concrete structure wall; 9) demoulding, curing, and acceptance of the wall.
[0058] Example 4 Preparation of Prefabricated Ancient Building Threshold Wall B
[0059] The preparation method in Example 3 was followed, except that the insulation layer material was replaced with polystyrene board. Other preparation methods were the same.
[0060] Effect test
[0061] Under the condition of an outdoor environment of 36℃, measurements were conducted on two houses with similar natural conditions and similar house configurations, which were made of wall A and wall B respectively. The indoor temperature of the former was 27℃, and the indoor temperature of the latter was 31℃.
[0062] Under the condition of an outdoor environment of 14℃, measurements were conducted on two houses with similar natural conditions and similar house configurations, which were made of wall A and wall B respectively. The indoor temperature of the former was 17℃, and the indoor temperature of the latter was 20℃.
[0063] It can be seen that the wall material prepared by using the expanded perlite board with phase change thermal insulation function of the present invention has good adaptive temperature regulation function and good flame retardancy compared with common thermal insulation materials.
Claims
1. A method for preparing an assembled ancient building wall with phase change thermal insulation function, characterized in that: The thickness of the prefabricated ancient building wall is 210-330mm, and it includes a 30-50mm face brick layer, a 40-60mm concrete outer page layer, a 60-100mm insulation layer and an 80-120mm concrete structure wall inner page layer from the outer wall to the inner wall; wherein the insulation material of the insulation layer is an expanded perlite board with phase change insulation function; the raw materials for preparing the expanded perlite board include 100 parts by weight of modified expanded perlite with phase change insulation function, 50-70 parts by weight of water glass type adhesive, 3-8 parts by weight of water repellent, 10-20 parts of fiber, and 10-30 parts by weight of water; the water glass type adhesive is composed of 40%-60% of sodium water glass, 20%-40% of potassium water glass, and 20%-30% of silica sol in weight percentage; the expanded perlite board is prepared by the following steps: Step A: premixing, mixing water glass type adhesive, water repellent, fiber and water evenly according to the raw material measurement to obtain premix A; Step B: mixing, mixing the premix A with the modified expanded perlite; Step C: pressing and molding, pressing and molding the slurry obtained in step B using a mold to obtain a slab; Step D: Drying and shaping, after demoulding, drying is carried out at a drying temperature of 70-120°C and a drying time of 7-12 hours, and an expanded perlite board with phase change thermal insulation function can be obtained and inspected.
2. The preparation method according to claim 1, characterized in that: The modified expanded perlite with phase change and heat preservation function is prepared as follows: 1) Infiltrating organic phase change material into expanded perlite; Add expanded perlite into a vacuum reactor at 40-60° C., then evacuate the vacuum reactor to a negative pressure of 0.06-0.08 MPa, close the exhaust valve, add liquid organic phase change material while stirring, and continue for 10-20 minutes; then open the exhaust valve, adjust the negative pressure of the vacuum reactor to 0.085-0.095 MPa, continue stirring to allow the organic phase change material to be fully adsorbed by the expanded perlite, and the time is 40-120 minutes; stop stirring, adjust to normal pressure to obtain organic phase change material composite expanded perlite A; Wherein, by weight, the expanded perlite: organic phase change material is 10: (6-9); Wherein, in the organic phase change material, the ratio of n-tetradecane:n-hexadecane:n-octadecane is 1:(0.5-1.5):(1-3) by weight; 2) at room temperature, mixing acrylic acid, sodium hydroxide, acrylamide, an initiator and water to obtain a reaction solution 1; The organic phase change material composite expanded perlite A prepared in step 1) is added to a reactor with a vacuum degree of 0.08-0.095 MPa, and the reaction solution 1 is added while stirring for 0.5-6 hours, and then the stirring is stopped to obtain the modified expanded perlite, and then the obtained modified expanded perlite is placed in a reactor under normal pressure and heated at a temperature of 70-90° C. for 0.5-1 hour to obtain the modified expanded perlite B; The mass ratio of acrylic acid, sodium hydroxide, acrylamide and organic phase change material composite expanded perlite A is (10-20): (4-8): (2-3): 100; the initiator is potassium persulfate or sodium persulfate; 3) At room temperature, acrylate, silane, photoinitiator and thermal initiator are added into a reaction kettle and stirred to obtain a reaction solution 2; the modified expanded perlite B prepared in step 2) is immersed in the above-mentioned reaction solution 2 while stirring for 30 minutes to 6 hours, and the stirring is stopped and filtered to obtain the modified expanded perlite and the filtrate, which can be reused; the obtained modified expanded perlite is then cured by UV radiation for 0.5-1 hour; the modified expanded perlite is then placed in an oven and heated for 20-40 minutes at a heating temperature of 70-90° C. to obtain a modified expanded perlite finished product with phase change and thermal insulation functions.
3. The preparation method according to claim 1, characterized in that: The preparation method of the assembled ancient building wall comprises the following steps: (1) cleaning the mold; (2) arranging bricks and filling the seams with sponge strips to obtain a face brick layer, and grooving the side of the face brick layer close to the concrete outer layer; (3) filling the seams with cement mortar; (4) brushing an interface agent on the side of the face brick layer close to the concrete outer layer; (5) laying the first layer of steel bars and setting upper and lower layer steel bar tie embedded parts; (6) pouring concrete to obtain a concrete outer layer; (7) laying a thermal insulation layer; (8) laying a second layer of steel bars, connecting the first layer of steel bars with the second layer of steel bars, and pre-embedding water and electricity pipelines, hanging parts, and connecting parts; (9) pouring the inner layer of the concrete structure wall; (10) demoulding, curing, and acceptance of the wall.
4. The preparation method according to claim 2, characterized in that: The silane is γ-methacryloxypropyltrimethoxysilane.
5. The preparation method according to claim 2, characterized in that: The thermal initiator is potassium persulfate or sodium persulfate.
6. The preparation method according to claim 2, characterized in that: The photoinitiator is benzoin ethyl ether, α, α-dimethoxy-α-phenylacetophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxy-cyclohexyl phenyl ketone, benzophenone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide or diarylphosphine oxide.
7. The preparation method according to claim 2, characterized in that: In the step 3), the mass ratio of acrylate, silane, photoinitiator, thermal initiator and modified expanded perlite B is (100-150):(40-50):(2-3):(2-3):
10.
8. The preparation method according to claim 1 or 2, characterized in that: The water repellent is an organic silicon water repellent; and the fiber is a polypropylene chopped fiber.
9. The preparation method according to claim 1 or 2, characterized in that: The wall is a sill wall, a gable wall or a rear eaves wall; the facing brick layer is made of small mud bricks.
Citation Information
Patent Citations
Alkali efflorescence inhibition perlite heat insulation plate and making method thereof
CN105439529A
Energy -saving archaize building roofing
CN207211470U
Preparation method of phase-change material microcapsule
CN101717618A
Foamed water glass expanded perlite thermal insulating board
CN103058623A
Heat-storage aerated concrete and preparation method thereof
CN105753390A